Propuesta de adopción de marketing digital para la transformación de la empresa Agroalmacen Animals del llano. (2022)
Marketing in companies has changed, with social evolution and global paradigms, the traditional concept of marketing has been left aside, where in recent years new terms have been heard and implemented, one of them and perhaps the most important is linked to digital transformation, which goes far beyond selling on digital platforms, generating in companies the need to be part of this new era of digital transformation, but being part of this era requires companies to adopt transformation mechanisms in all their processes, seeking to meet the needs of customers and with the defined objective of business growth, thus changing the way to reach each of them; Likewise, it is important to diagnose where the company is, what changes should be made in its value chain, process map, supply chains, distribution channels and in general in its workflow. It is also vital to work with 12 each of the employees and managers as they are directly related to the use of these digital tools that seek to add value to internal processes. On the other hand, to strengthen the company's participation in the use and management of social networks. This digital transformation allows the company to participate in a competitive market within an economic environment that is constantly changing with technological advances and the introduction of new companies and business models. This work is done in order to create a digital marketing strategy for the store Animals del Llano since they do not have information and knowledge of digital tools that allow them to increase their productivity, have greater recognition and in turn position themselves in the digital world